Knowledge Management and Acquisition for Intelligent Systems 12th Pacific Rim Knowledge Acquisition Workshop, PKAW 2012, Kuching, Malaysia, September 5-6, 2012. Proceedings - Richards, Deborah; Kang, Byeong Ho.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the proceedings of the 12th International Workshop on Knowledge Management and Acquisition for Intelligent Systems, PKAW 2012, held in Kuching, Malaysia, in September 2012. The 21 full papers and 11 short papers included in this volume were carefully reviewed and selected from 141 papers. They deal with knoweldge acquisition issues and evaluation; language, text and image processing; incremental knowledge acquisition; agent based knowledge acquisition and management; ontology-based approaches; WEB 2.0 methods and applications; and other applications.
Constraints Dependent T-Way Test Suite Generation Using Harmony Search Strategy -- Evaluating Disaster Management Knowledge Model by Using a Frequency-Based Selection Technique -- Perceptual Evaluation of Automatic 2.5D Cartoon Modelling -- Automatic Acquisition of User Models of Interaction to Evaluate the Usability of Virtual Environments -- User-Centric Recommendation-Based Approximate Information Retrieval from Marine Sensor Data -- Addressing Challenges for Knowledge Discovery from Data in the Domain of Seaport Integration -- Data Envelopment Analysis for Evaluating Knowledge Acquisition and Creation -- Language, Text and Image Processing A High-Order Hidden Markov Model for Emotion Detection from Textual Data -- A Lazy Man$1 (Bs Way to Part-of-Speech Tagging -- Knowledge Acquisition for Categorization of Legal Case Reports -- Extraction of How-to Type Question-Answering Sentences Using Query Sets -- Image Indexing and Retrieval with Pachinko Allocation Model: Application on Local and Global Features -- Detection of CAN by Ensemble Classifiers Based on Ripple Down Rules -- Improving Open Information Extraction for Informal Web Documents with Ripple-Down Rules -- Ripple-Down Rules with Censored Production Rules -- RM and RDM, a Preliminary Evaluation of Two Prudent RDR Techniques -- Agent Based Knowledge Acquisition and Management Planning Children$1 (Bs Stories Using Agent Models -- A Framework for a Multi-agent Collaborative Virtual Learning Environment (MACVILLE) Based on Activity Theory -- Emergence of Personal Knowledge Management Processes within Multi-agent Roles -- Ontology-Based Approaches Towards an Ontology-Based Approach to Knowledge Management of Graduate Attributes in Higher Education -- Commonsense Knowledge Acquisition through Children$1 (Bs Stories -- Externalizing Senses of Worth in Medical Service Based on Ontological Engineering -- Web 2.0 Methods and Applications Crowd-Sourced Knowledge Bases -- Social Issue Gives You an Opportunity: Discovering the Personalised Relevance of Social Issues -- Identifying Important Factors for Future Contribution of Wikipedia Editors -- Network Analysis of Three Twitter Functions: Favorite, Follow and Mention -- User-Oriented Product Search Based on Consumer Values and Lifestyles -- Extracting Communities in Networks Based on Functional Properties of Nodes -- Revealing and Trending the Social Knowledge Studies -- Workflow Knowledge Sharing through Social Networks -- Identifying Characteristics of Seaports for Environmental Benchmarks Based on Meta-learning -- A Situated Experiential Learning System Based on a Real-Time 3D Virtual Studio.s
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Information systems; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing